A frontier in the use of camera traps: surveying terrestrial squamate assemblages. Issue 3 (4th August 2017) - Welbourne, Dustin J.; Paull, David J.; Claridge, Andrew W.; Ford, Frederic
Abstract: There is an urgent need to improve methods for surveying snakes and lizards (squamates). Currently, fundamental data gaps exist about squamate distributions and abundance in numerous regions. Traditional squamate survey methods are useful, but they are also resource and labour intensive. In recent decades, camera traps have provided researchers an effective, cost‐efficient and minimally invasive survey tool; albeit primarily for birds, mammals and fish. The use of camera traps for reptiles generally, and squamates specifically, has been limited. Yet, recent developments in camera trapping methodology demonstrate how they could be used to survey a squamate assemblage. Although further research is required, these developments are encouraging. Thus, surveying squamates with camera traps is a primary frontier in camera trapping. Abstract : There is an urgent need to improve methods for surveying snakes and lizards (squamates). Currently, fundamental data gaps exist about squamate distributions and abundance in numerous regions. Traditional squamate survey methods are useful, but also resource intensive due to their labour‐intensive nature. In recent decades, camera traps have provided researchers an effective, cost‐efficient and ethical survey tool; albeit primarily for birds, mammals and fish. The use of camera traps for reptiles generally, and squamates specifically, has been limited. Nevertheless, recent developments in camera trapping methodology demonstrate how they can be used to survey a squamate assemblage. Although further research is required, these developments are encouraging. Therefore, surveying squamates with camera traps is a key future frontier in camera trapping.